Counter striking psychosis: Commercial video games as potential treatment in schizophrenia? A systematic review of neuroimaging studies. (September 2016) - Suenderhauf, Claudia; Walter, Anna; Lenz, Claudia; Lang, Undine E.; Borgwardt, Stefan
Highlights: This review summarizes recent MRI studies assessing video game studies and compares their effect to CRT induced brain modulations. Video game studies are heterogeneous in design and results, but some commonalities with CRT induced brain effects can be seen. A discussion of schizophrenia-specific vulnerabilities impeding video game training is provided. Limited number and heterogeneity of video game studies impedes meta-analytical assessments which allows more generalizable conclusions. Abstract: Schizophrenia is a severe, chronic, and strongly disabling neuropsychiatric disorder, characterized by cognitive decline, positive and negative symptoms. Positive symptoms respond well to antipsychotic medication and psycho-social interventions, in contrast to negative symptoms and neurocognitive impairments. Cognitive deficits have been linked to a poorer outcome and hence specific cognitive remediation therapies have been proposed. Their effectiveness is nowadays approved and neurobiological correlates have been reconfirmed by brain imaging studies. Interestingly, recent MRI work showed that commercial video games modified similar brain areas as these specialized training programs. If gray matter increases and functional brain modulations would translate in better cognitive and every day functioning, commercial video game training could be an enjoyable and economically interesting treatment option for patients with neuropsychiatric disorders. This systematic review summarizes advances in the area with emphasis on imaging studies dealing with brain changes upon video game training and contrasts them to conventional cognitive remediation. Moreover, we discuss potential challenges therapeutic video game development and research would have to face in future treatment of schizophrenia.